Middle Ordovician (Darriwilian) cheirurid trilobites from the Table Cove Formation, western Newfoundland, Canada - Adrain, Jonathan M.; Pérez-Peris, Francesc (Zootaxa, 2021)
A diverse mid-Darriwilian trilobite fauna from the Table Cove Formation, western Newfoundland, has long been known on the basis of calcareous specimens from the west coast of the Great Northern Peninsula. Discovery of silicified faunas in localities on the east coast provides additional morphological information for previously known species, and also reveals the presence of multiple new genera and species. Many of these species are important, as they represent some of the earliest Laurentian members of the diversifying Whiterock Fauna, and seem phylogenetically near to the base of their respective clades. The concept of Sphaerexochinae is restricted to the genus Sphaerexochus itself, with the possible inclusion of Newfoundlandops n. gen. (type species N. karimae n. sp.), which shares with Sphaerexochus potential synapomorphies including the structure of the hypostome and the presence of fine granular sculpture on the librigenal border and field. Most of the Early and Middle Ordovician taxa with three pygidial segments previously classified as Sphaerexochinae by many authors are reassigned to Acanthoparyphinae on the basis of multiple putative synapomorphies. Other new cheirurid genera from the Table Cove Formation are the pilekiine Harebayaspis n. gen. (type species H. plurima n. sp.), and the deiphonine Mainbrookia n. gen. (type species M. becki n. sp.). Other species revised or described include the cheirurine Laneites polydorus (Billings, 1865), and the acanthoparyphines Cydonocephalus tiffanyae n. sp., Kawina stougei n. sp., and Kawina? sp.